2020
DOI: 10.1080/15592324.2020.1820681
|View full text |Cite
|
Sign up to set email alerts
|

Trichostatin A and sodium butyrate promotes plant regeneration in common wheat

Abstract: Histone acetylation modification plays a vital role in plant cell division and differentiation. However, the function on wheat mature embryo culture has not been reported. Here, we used the mature embryo of wheat genotypes including CB037, Fielder, and Chinese Spring (CS) as materials to analyze the effects of different concentrations of trichostatin A (TSA) and sodium butyrate (SB) on plant regeneration efficiency. The results showed that, compared with the control group, the induction rates of embryogenic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Specifically, the use of Trichostatin A induced microspore embryogenesis in wheat [ 142 ] and somatic embryogenesis in Arabidopsis [ 143 ]. Treatment by trichostatin A and sodium butyrate also improved regeneration efficiency from mature wheat embryos [ 144 ]. It can be concluded that utilisation of epigenetically active substances is focused on topics, where it is suspected that the level of DNA methylation or acetylation of histones play a role in the respective phenomena.…”
Section: Epigenetic Advances In Crop Improvement: Exploiting Epigenetic Diversitymentioning
confidence: 99%
“…Specifically, the use of Trichostatin A induced microspore embryogenesis in wheat [ 142 ] and somatic embryogenesis in Arabidopsis [ 143 ]. Treatment by trichostatin A and sodium butyrate also improved regeneration efficiency from mature wheat embryos [ 144 ]. It can be concluded that utilisation of epigenetically active substances is focused on topics, where it is suspected that the level of DNA methylation or acetylation of histones play a role in the respective phenomena.…”
Section: Epigenetic Advances In Crop Improvement: Exploiting Epigenetic Diversitymentioning
confidence: 99%
“…Indeed, both auxin treatment and wounding stress alter histone modifications, including histone acetylation, which positively regulates the expression of cellular reprogramming-related genes Yamamuro et al 2016). Trichostatin A (TSA) and butyric acid (BUA), well-known inhibitors of histone deacetylases (HDACs) that increase the level of acetylated histones, can be added during tissue culture to enhance plant tissue regeneration (Bie et al 2020;Lee et al 2020;Li et al 2014;Wójcikowska et al 2018). TSA treatment additionally alters auxin responsiveness (Li et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hyper-acetylation of histones by HATs weakens the interaction between histones and DNA and loosens the chromatin structure, leading to transcriptional activation, whereas hypo-acetylation of histones by HDACs compacts chromatin structure and results in transcriptional repression (Kumar et HDAC families . In plants, treatment with HDACi, mainly the pan Rpd3/hda1 inhibitor trichostatin A (TSA), has helped define the role of histone acetylation in different developmental processes, including seed germination Tai et al, 2005;, root and leaf development , as well as in induced totipotency and pluripotency (Abrahamsson et al, 2017;Bie et al, 2020;Castillo et al, 2020;Wójcikowska et al, 2018).…”
Section: Epigenetic Regulation Of Embryogenesismentioning
confidence: 99%
“…HDACi that target Rpd3/Hda1 and HD2-type HDACs, inhibit HDAC activity by interacting with zinc ion and active site residues in the catalytic domain (Miller et al, 2003). In plants, treatment with HDACi, mainly the pan Rpd3/hda1 inhibitor trichostatin A (TSA), uncovered roles for histone acetylation in a range of developmental processes, including seed germination Tai et al, 2005;, root and leaf development , as well as in in vitro plant regeneration (Abrahamsson et al, 2017;Bie et al, 2020;Castillo et al, 2020;Wójcikowska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%